Beauty parlor stroke revisited: An 11-year single-center consecutive series. Issue 3 (April 2016) - Correia, Pamela N; Meyer, Ivo A; Eskandari, Ashraf; Michel, Patrik
Background: Hairdresser-related ischemic cerebrovascular events (HICE) are attributed to compression of vertebral arteries or cervical artery dissections. We determined their frequency, mechanisms, localization and outcome in a pre-specified study. Methods: We prospectively collected ischemic strokes and transient ischemic attacks occurring in relation to a hairdresser visit from 2002 to 2013, using consecutive data from an ischemic stroke registry (ASTRAL). HICE were compared to all other acute ischemic strokes in ASTRAL. Results: We identified 10 HICE (9 strokes and 1 transient ischemic attack). Age and anterior-posterior distribution were similar with a significantly higher rate of females (90% vs. 43%, p = 0.02) in the HICE group compared to ASTRAL. Patients with HICE had significantly lower incidence of hyperlipidemia (30% vs. 73%) and diabetes (0% vs. 19%). The mechanisms of HICE were diverse: carotid artery dissection ( n = 2), cardiac ( n = 2), lacunar ( n = 2), other determined ( n = 2) and unknown etiology ( n = 2). Two HICE with atherosclerotic intracranial disease were possibly caused by acute hemodynamic changes related to systemic hypotension during hot air hair drying. Unadjusted favorable outcome at three months seemed to be better in HICE (90% vs. 57%), and 12-month mortality and recurrences were similar. Conclusions: HICE may occur frequently in females without a predilection for the posterior circulation. Although some HICE may occur by chance (pseudo-HICE), hairdresser visits may have a causal role in some cases, including cervical artery dissection or hemodynamic compromise related to pre-existing arterial disease (true HICE). Available data are insufficient for specific preventive recommendations.